Reflections on Brexit - Ahmad, Khairil Izamin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
I begin with my personal stake on the issue. In a way, without wishing to be overly sentimental, the European Union (EU) has had a hand in the creation of my family. I met my wife, a Swedish citizen, in Britain while studying for a Master’s and later a PhD degree. She, along with many friends who I met there, are part of a generation of Europeans who have benefited from the ease in cross border mobility that came with the EU. Far from diminishing the national identities of its citizens, the EU has managed to allow national belongings to be expressed through its presence. My wife, for one, is a proud Swede who also identifies as a European citizen.